PLURALITY OF RELIGION: Future Challenges of Religion and Democracy in Indonesia (State Islamic University (UIN) of Sunan Ampel Surabaya, 2015)
Religious pluralism is a necessity. In Indonesia, there are six officially recognized religions, and some religious denominations. In the context of the challenges of democracy, religion in Indonesia faces daunting challenges This paper focuses on two challenges facing the religions related to the conception of democracy in Indonesia, namely the problem of understanding of religious teachings and politicization of religion. In the context of understanding religious teachings, believers interpret them correctly through exploring the substantial meaning, particularly in understanding religious doctrines regarding to the values of justice, human rights, democratization, and so forth. Furthermore, religion is understood as the truth rather than as an identity and a symbolic form. This is because understanding religion as an identity tends to create conflicts. In regard to the politicization of religion, religious followers provide a basis for common purpose and values that can help maintain a society's political life and national solidarity as well as control to the political system.